Antonio Gramsci and Fund of Knowledge: Organic Ethnographers of Knowledge in Workers' Centres - Zanoni, Joseph P. (International Gramsci Journal, 2023)
Participants of workers’ centres, led by organic ethnographers of knowledge, will be engaged in a critique of spontaneous funds of knowledge and the development of judgment criteria to guide workers from Gramsci’s conception of common sense to good sense in the discovery of knowledge through praxis.